Functional modelling in evolvable assembly systems - Sanderson, David; Chaplin, Jack C.; Ratchev, Svetan (2018)
The design and reconfiguration of adaptive production systems is a key driver in modern advanced manufacturing. We summarise the use of an ap-proach from the field of functional modelling to capture the function, behaviour, and structure of a system. This model is an integral part of the Evolvable Assembly Systems architecture, allowing the system to adapt its behaviour in response to changing product requirements. The integrated approach is illustrated with an example taken from a real EAS instantiation.